The Effectiveness Of Ginging Ginger Candy Towards Nausea And Vomiting In Pregnant Women In Air Teluk Ki Village In 2022 - maidina putri; Rewa Maframi (Institute of Computer Science (IOCS), 2022)
Nausea and vomiting (emesis gravidarum) are symptoms that often appear in the 1st trimester of pregnancy, nausea usually occurs in the morning, but can also occur every day and night, this occurs due to relaxation of the digestive muscles, including peristalsis in the stomach so that food is digested. by the stomach it becomes longer and peristalsis is easy to return to the esophagus, besides that it is also due to the influence of the HCG hormone. In Air Teluk Kiri Village as many as 30 pregnant women experience nausea and vomiting, various ways are done to overcome nausea and vomiting, one of which is giving candy ginger. The aim was to analyze the effect of ginger candy on the reduction of emesis gravidarum in pregnant women in Air Teluk Kiri Village. The research method used is pre-experimental research with a static group comparison/posttest only control group design, using a sample of 30 respondents. The instrument used to measure nausea and vomiting is an observation sheet. The data was collected by the researcher himself and the data were analyzed univariately and bivariately using the Mann Whitney test. The results showed that there was an effect of ginger candy on emesis gravidarum in pregnant women with p value (p = 0.001, = 0.05). Conclusions from this study There is an effect of ginger candy on reducing nausea and vomiting in first trimester pregnant women in Air Teluk Kiri Village. It is hoped that ginger candy can be an alternative choice in overcoming emesis gravidarum in pregnant women in 2022 The instrument used to measure nausea and vomiting is an observation sheet. The data was collected by the researcher himself and the data were analyzed univariately and bivariately using the Mann Whitney test. The results showed that there was an effect of ginger candy on emesis gravidarum in pregnant women with p value (p = 0.001, = 0.05). Conclusions from this study There is an effect of ginger candy on reducing nausea and vomiting in first trimester pregnant women in Air Teluk Kiri Village. It is hoped that ginger candy can be an alternative choice in overcoming emesis gravidarum in pregnant women in 2022 The instrument used to measure nausea and vomiting is an observation sheet. The data was collected by the researcher himself and the data were analyzed univariately and bivariately using the Mann Whitney test. The results showed that there was an effect of ginger candy on emesis gravidarum in pregnant women with p value (p = 0.001, = 0.05). Conclusions from this study There is an effect of ginger candy on reducing nausea and vomiting in first trimester pregnant women in Air Teluk Kiri Village. It is hoped that ginger candy can be an alternative choice in overcoming emesis gravidarum in pregnant women in 2022 The results showed that there was an effect of ginger candy on emesis gravidarum in pregnant women with p value (p = 0.001, = 0.05). Conclusions from this study There is an effect of ginger candy on reducing nausea and vomiting in first trimester pregnant women in Air Teluk Kiri Village. It is hoped that ginger candy can be an alternative choice in overcoming emesis gravidarum in pregnant women in 2022 The results showed that there was an effect of ginger candy on emesis gravidarum in pregnant women with p value (p = 0.001, = 0.05). Conclusions from this study There is an effect of ginger candy on reducing nausea and vomiting in first trimester pregnant women in Air Teluk Kiri Village. It is hoped that ginger candy can be an alternative choice in overcoming emesis gravidarum in pregnant women in 2022